El programa páginas del recuerdo trasmitido por TVS canal 13 los días sábados a las 20:30, y su incidencia en el imaginario de los habitantes del cantón Riobamba comprendido entre los 40 a 70 años de edad en el período junio-diciembre del 2015. - Martínez Taboada, Fernando Daniel (2017)
This research corresponds to the theme: "The Pages of Remembrance program transmitted by TVS channel 13 on Saturdays at 8:30 p.m., and its incidence in the imaginary of the inhabitants of the canton Riobamba between 40 and 70 years of age in the Period June-December 2015 ", its objective is to determine the incidence of the Pages of Remembrance program in the imaginary of the inhabitants of Riobamba, which is related to romantic music, its symbolism and identification of the character who led the program. Next, the theoretical framework approach related to the independent variable is the Pages of Remembrance program, where reference is made to theories, models and schools of communication, elements and components; The dependent variable is the imaginary of the inhabitants of the canton Riobamba with its titles and subtitle referring to the subject, continues with the glossary of terms, hypotheses, operationalization of variables. The research methodology (research, scientific, inductive, deductive), research design (non-experimental and descriptive), type of research (explanatory, field and bibliographic), research Diagnostic and exploratory), the population is of 36,301 inhabitants with a sample of 396 citizens, for this the technique of the survey and interview accompanied by the instruments that are the survey guide and interview guide were applied. Related to the analysis and interpretation of results are the statistical tables and graphs drawn up with the data obtained from the survey, to later carry out the verification of the hypothesis through the arithmetic mean, from which the conclusions and recommendations are obtained. The results achieved are precisely the impact it had on the citizens between the ages of 40 and 70, because they remember with great enthusiasm the romantic music, ballads, rock and more musical genres that have made history, also revive special moments of certain Events such as infatuation, radio messages and night serenades, mainly echo the name of Mr. Fernando Martinez who led the program Páginas del Recuerdo on TVS channel 13 of the city of Riobamba.